The KEAP1/NRF2 axis controls LPS-induced oxidative stress, inflammasome activation and caspase-1 activity in human endothelial cells - Alba Montero-Jodra; Maria Jesús Estebán-Amo; Silvia Patricia Fernández-Martínez; César García Martínez; Miguel Ángel de la Fuente García; Adrián García-Concejo; Marta Martin-Fernandez; Eduardo Tamayo; María Simarro (PLoS ONE, 2026)
Endothelial cells play a critical role in the inflammatory response during sepsis, however, their metabolic adaptations to inflammatory stimuli remain much less characterized compared to immune cells. Here, we demonstrate that Human Umbilical Vein Endothelial Cells (HUVECs) do not undergo the metabolic and respiratory rewiring typically observed in macrophages following lipopolysaccharide (LPS) stimulation, a common model of inflammation during sepsis. A key metabolite in LPS-activated macrophages is itaconate, which is known for its anti-inflammatory properties. Although HUVECs do not naturally produce itaconate, we explored whether exogenous administration of the cell-permeable derivative 4-octyl itaconate (4-OI) could modulate their response to LPS. Remarkably, 4-OI treatment significantly reduced mitochondrial reactive oxygen species (mitoROS) levels in LPS-treated HUVECs, restoring them to baseline levels. This antioxidant effect was accompanied by a pronounced decrease in inflammasome activation, including suppression of ASC speck formation and caspase-1 activation. These findings suggest that 4-OI could protect endothelial cells from inflammation during sepsis in a manner similar to its role in macrophages. Mechanistically, 4-OI acts through the KEAP1/NRF2 antioxidant pathway. Silencing of KEAP1, the direct molecular target of 4-OI, resulted in a pronounced upregulation of NRF2 target genes, particularly HMOX1, with modest effects on NQO1 and no change in GCLC. NRF2 knockdown decreased HMOX1 expression and blunted 4-OI’s effects, although some residual induction persisted. Further confirming the importance of this pathway, KEAP1 silencing itself suppressed LPS-induced mitoROS, ASC speck formation, and caspase-1 activation, mimicking 4-OI treatment. Taken together, these results demonstrate that 4-OI protects endothelial cells from LPS-induced oxidative stress and inflammation primarily via the KEAP1/NRF2 axis.